2.6 REDUCING EQUATIONS TO SIMPLER FORMS

When linear equations are in fractions then we can reduce them to a simpler form by  –

Taking the LCM of the denominator

Multiply the LCM on both the sides, so that the number will reduce without the denominator and we can solve them by the above methods.

Example :Solve the linear equation : Solution: As the equation is in complex form, we have to reduce it into a simpler form.

Step 1: Take the L.C.M. of the denominators, 2,  3,  4, and  5, which is 60.
Step 2: Multiply both the sides by 60  , 30x −12    =    20 x  +  15  +  60

Step 3. Bring all the variables on the LHS and all the constants on the RHS

30 x – 20 x    =    15  +  12  +  60

10 x    =    87

Step 4: Dividing both the sides by 10

x    =    8.7

Exercise 2.5

Solve the following linear equations.

1. x / 2 –  1 / 5    =   x / 3   +   ¼

Solution:   x / 2  –  1 / 5    =   x / 3   +   ¼

⇒        x / 2    –   x / 3    =    ¼  +  1 / 5

⇒      ( 3 x   –   2 x) / 6    =    (5  +  4) / 20

⇒      3 x    –   2 x    =    9 / 20 × 6

⇒        x    =    54 / 20

⇒        x    =    27 / 10

1.   n / 2 –  3 n / 4  +  5 n / 6    =    21

Solution:   n / 2  –  3 n / 4  +  5 n / 6    =    21

⇒      ( 6 n  –  9 n  +  10 n ) / 12    =    21

⇒      7 n / 12    =    21

⇒      7 n    =    21 × 12

⇒      n    =    252 / 7

⇒      n    =    36

1.   x +  7  –  8 x / 3    =    17 / 6  –  5 x / 2

Solution:   x  +  7  –  8 x / 3    =    17 / 6  –  5 x / 2

⇒        x   –   8 x / 3   +   5 x / 2    =    17 / 6  –  7

⇒      (6 x  –  16 x   +  15  x) / 6    =    (17  –  42)  / 6

⇒      5 x / 6    =     –  25 / 6

⇒      5 x    =     –  25

⇒        x    =     –  5

1.  ( x – 5) / 3    =    ( x  –  3) / 5

Solution:   ( x  –  5 ) / 3    =    ( x  –  3) / 5

⇒      5 ( x   –  5)    =    3 ( x  –  3)

⇒      5 x  –  25    =    3 x  –  9

⇒      5 x  –  3 x    =  –  9  +  25

⇒      2 x    =    16

⇒        x      =    8

1.   ( 3 t – 2) / 4  –  ( 2 t  +  3 ) / 3    =    2 / 3  –  t

Solution:  ( 3 t  –  2) / 4  –  ( 2 t  +  3) / 3    =    2 / 3  –  t

⇒      ( 3 t  –  2) / 4) × 12  –  ( 2 t  +  3) / 3) × 12

⇒      ( 3 t  –  2) × 3  –  ( 2 t  +  3) × 4    =    2 × 4  –  12 t

⇒      9 t   –  6  –  8t  –  12    =    8  –  12 t

⇒      9 t   –  6  –  8t  –  12    =    8  –  12 t

⇒      t  –  18    =    8  –  12 t

⇒      t  +  12 t    =    8  +  18

⇒      13 t    =    26

⇒        t    =    2

1.   m –  (m  –  1) / 2    =    1  –  (m  –  2) / 3

Solution:   m  –  (m  –  1) / 2    =    1  –  (m  –  2) / 3

⇒        m  –  m / 2  –  1 / 2    =    1  –  (m / 3  –  2 / 3)

⇒        m  –  m / 2  +  ½    =    1  –  m / 3  +  2 / 3

⇒      m  –  m / 2  +  m / 3    =    1  +  2 / 3  –  ½

⇒      m / 2  +  m / 3    =    ½  +  2 / 3

⇒      ( 3m  +  2m ) / 6    =    (3  +  4) / 6

⇒      5m / 6    =    7 / 6

⇒      m    =    7 / 6 × 6 / 5

⇒      m    =    7 / 5

Simplify and solve the following linear equations.

1.    3 ( t –  3 )    =    5 ( 2 t  +  1)

Solution:   3 ( t  –  3)    =    5 ( 2 t  +  1)

⇒        3 t  –  9    =    10 t  +  5

⇒      3 t  –  10 t    =    5  +  9

⇒      –  7 t    =    14

⇒      t    =    14 /   –  7

⇒      t    =  –  2

1.   15 ( y  –  4 ) –2 ( y  –  9)  +  5 ( y  +  6 )    =    0

Solution:   15(y  –  4) –2(y  –  9)  +  5(y  +  6)    =    0

⇒      15y  –  60   –  2y  +  18  +  5y  +  30    =    0

⇒      15y  –  2y  +  5y    =    60  –  18  –  30

⇒      18y    =    12

⇒       y    =    12 / 18

⇒       y    =    2 / 3

1.   3 (5 z –  7)  –  2 ( 9 z  –  11)    =    4 ( 8 z  –  13 )  –  17

Solution:   3(5 z  –  7)  –  2(9 z  –  11)    =    4 ( 8 z  –  13)  –  17

⇒        15 z  –  21  –  18 z  +  22    =    32 z  –  52  –  17

⇒      15 z  –  18 z  –  32 z    =  –  52  –  17  +  21  –  22

⇒       –  35 z    =  –  70

⇒       z    =   –  70 /   –  35

⇒       z    =    2

1.   0.25 ( 4 f  –  3)    =    0.05 ( 10 f  –  9)

Solution:    0.25(4f  –  3)    =    0.05(10f  –  9)

⇒      f  –  0.75    =    0.5f  –  0.45

⇒      f  –  0.5f    =  –  0.45  +  0.75

⇒      0.5 f    =    0.30

⇒        f    =    0.30 / 0.5

⇒      f    =    3 / 5

⇒      f    =    0.6.